Розвиток категоріально-понятійного апарату антикризового управління в контексті синергетичної парадигми - Шалений, Володимир (Odesa National University of Technology, 2024)
The article carries out a comprehensive study of the categorical-conceptual apparatus transformation of the anti-crisis management under the influence of the synergistic paradigm, which takes into account modern approaches to the analysis of complex systems. Special attention is paid to justifying the need to rethink traditional definitions and concepts of anti-crisis management in the light of the non-linear nature of economic processes, as well as emergent properties that arise in the dynamics of complex systems. The article reveals a new meaningful content of the basic concepts of "crisis" and "anti-crisis management", which allows us to consider the crisis not only as a threat, but also as a natural stage in the evolution of the system, which serves as a bifurcation point. At such points, the system receives unique opportunities for qualitative renewal and transition. Special attention is paid to the development of the concept of "anti-crisis resilience", which is interpreted as the system's ability to maintain viability due to effective adaptation, transformation and use of internal potential. Within the framework of the study, new concepts were introduced and substantiated, such as "synergistic effect of crisis", which demonstrates the positive potential of crisis phenomena, "anti-crisis resilience" as the system's ability to quickly recover after crises, as well as "transformational crisis", which contributes to the reset of management mechanisms. Additionally, the content of the concepts "anti-crisis potential", "crisis diagnostics" and "anti-crisis monitoring" from the standpoint of the theory of complex systems has been clarified, which allows for a deeper understanding of the mechanisms of their interaction and influence on decision-making. The article reveals the relationship between key concepts that form the theoretical and methodological basis of anti-crisis management in the conditions of non-linear dynamics of economic processes. Prospective directions for the further development of the categorical-conceptual apparatus, aimed at providing a deeper understanding of the mechanisms of self-organization.